Pengembangan Desain Interaksi Mesin Pencatat Untuk Tunanetra Dengan Fitur Text-to-Speech Berbasis Raspberry Pi - Nafisa Nafisa; Hurriyatul Fitriyah; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Recording is one of the commonly learning methods used by the students and also students with blind disability. To record, students with blind disability used a difficult manual recorder and takes a long time. Therefore, computerized records related tools are urgently needed. To facilitate students with blind disability in the process of recording, a recorder machine is made using the design principles in the layout. The process of making is done by the method of what is wanted, analysis, design and process of application of interaction design principles. This recording machine consisted of 16 push buttons, character input using multi touch 6 buttons as a combination of braille letters. Then processed by Raspberry Pi and output audio on headset also the flashdisk as a sending medium. There is also function of adding, editing, searching, deleting, sending documents, enter, spaces, backspace and audio tools usage guide. On the duration of each tool function, an average of 1 minute 59.94 seconds on the overall scenario of the tool that is done every user both who are familiar with the typewriter or not. In the usability, the USE level obtained mode value 4 (agree) and design principle level obtained value of mode 5 (strongly agree) from likert scale 1-5. So it can be concluded that this tool has a high level of usabillity.